Resource Based View (RBV) Strategic Plan at Private School in Indonesia - Dwikamayuda, Dewa Made; Agung, Anak Agung Gede; Sulindawati, Ni Luh Gede Erni; Dantes, Kadek Rihendra (Lingeduca: Journal of Language and Education Studies, 2024)
This study addresses the need for a sustainable competitive advantage at a Christian school in Salatiga by developing a strategic plan based on the Resource-Based View (RBV). The research aimed to identify key internal resources that could strengthen the school's long-term success. Employing a research and development (R&D) approach, the study followed seven stages: identifying potential and problems, collecting data, designing the product, validating the design, revising the design, conducting limited product testing, and making final revisions. Data collection methods included interviews, observations, document studies, and focus group discussions (FGD), with data validated through triangulation of techniques and sources. The results highlighted a strategic plan centered on enhancing seven key internal resources: financial, physical, human, organizational, technological, innovation and creativity, and reputation resources. The study concludes with a recommendation that the foundation, principals, teachers, staff, and school committee actively support and optimize the strategic plan's implementation for sustained success.